Investigation of the Attitudes of Academicians towards Sports - Karahuseyinoglu, M. Fatih (Asian Journal of Education and Training, 2019)
The purpose of this study is to investigate the attitudes of academicians towards sports at Firat University, 191 academicians participated in the investigation as part of our study. "Attitude Scale towards Sports" was used to determine the attitudes of the academicians participating in the study towards sports. The scale is designed in likert type 5 grading, consisting of 22 substances and "Psychosocial, Physical and Mental Development" consisting of 3 sub-dimensions. In line with the study findings, academicians at Firat University have a general score of 1 to 5 scale scoring is x̄= 3.93, "Mental Development" sub-dimension size is x̄= 3.53, "Psycho-social Development" sub-dimension size is x̄= 3.98, and "Physical Development" sub-dimension size with an average of x̄= 4.08 was observed to have high attitude levels towards sports. There was a statistically significant difference in terms of attitude levels towards sports and age, participation in sports, title and working year variables for Academicians at Firat University. According to the gender variable, it was not found that the attitudes of academicians towards sports were not statistically significant. Academicians’ attitudes towards sports are very important. Students often see their instructors as their cult figure. Academicians’ attitudes towards sports are thought to make them feel good about themselves in terms of health and will be a positive example for students who consider themselves cult figures.